Phytoextraction of Cu, Zn, and Pb Enhanced by Chelators with Vetiver (Vetiveria zizanioides): Hydroponic and Pot Experiments. (1st March 2012) - Chen, K. F.; Yeh, T. Y.; Lin, C. F.
Abstract : Phytoextraction is a green remediation technology for clean-up contaminated soils. The effect of chelator application including EDTA, EDDS, and citric acid on phytoextraction of Cu, Zn, and Pb into high biomass vetiver ( Vetiveria zizaniodides ) was investigated in the hydroponic experiment and the pot experiment. In the hydroponic test, EDTA induced the most significant toxic symptom on vetiver compared to EDDS and citric acid. Obvious biofilm was attached in the rhizosphere of vetiver with the citric acid addition due to its serving as growth substrate while EDTA posed microbial toxicity to present clear solution. Sequential extraction results demonstrated that EDTA was better than EDDS and citric acid to change the adsorbed metal to loosely bound fraction which is more mobile and bioavailable. In the pot experiment, the critical finding was that vetiver has been demonstrated as a hyperaccumulator for treatment of EDDS with Cu; EDDS, citric acid, and EDTA with Zn; EDTA with Pb. EDDS and EDTA possess the viable phytoextraction ability and can be employed as an remediation alternative, though the groundwater leaching needs to be taken into serious consideration.